Endothelial and Platelet Function in Children With Previous Kawasaki Disease. (September 2014) - Laurito, Marianna; Stazi, Alessandra; Delogu, Angelica B.; Milo, Maria; Battipaglia, Irma; Scalone, Giancarla; Infusino, Fabio; Villano, Angelo; Russo, Giulio; Iannotta, Rossella; Saracino, Annalisa; Parrinello, Rossella; et al.
We investigated whether children with a previous Kawasaki disease (KD) have evidence of abnormal vascular and/or platelet function. We included 14 patients with previous KD and 14 matched controls. We assessed endothelial function by flow-mediated dilation (FMD), carotid intima–media thickness (cIMT), coronary microvascular function by coronary blood flow response (CBFR) to cold pressor test, and platelet reactivity by measuring monocyte–platelet aggregates (MPAs) and CD41-platelet expression by flow cytometry. No differences were found between the groups in FMD, cIMT, or CBFR to cold pressor test. The MPAs were similar in patients with KD and controls. CD41-platelet expression, however, was significantly increased in patients with KD compared with controls, both at rest (14.3 ± 1.9 vs 12.4 ± 1.9 mean fluorescence intensity [mfi], P = .01) and after adenosine diphosphate stimulation (19.3 ± 1.3 vs 17 ± 1.7 mfi, P < .001). In conclusion, children with a previous episode of KD showed increased platelet activation, compared with healthy participants despite no apparent vascular abnormality at follow-up.